1985
DOI: 10.1111/j.1469-7610.1985.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mentally Handicapped Children on Families–a Conceptual Review

Abstract: Recent research which examines the effects of mentally handicapped children upon families is reviewed. The studies are grouped into three categories based on the underlying conceptions which appear to guide them. The first category examines which families are most vulnerable to the presumed stress of a mentally handicapped child. The second category emphasises the material and practical problems families experience. The third category stresses the competence of families and describes the resources used to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
63
0
6

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(75 citation statements)
references
References 42 publications
6
63
0
6
Order By: Relevance
“…Patterson's early work, which examined coercive interaction with mothers, fathers, and siblings, indicated that mothers were the most common partners in coercive exchanges with their aggressive child (Patterson, 1980). Studies of families of children with disabilities show that mothers assume a larger portion of caregiving responsibilities for the child (see Byrne & Cunningham, 1985). Our initial assessment of routines was consistent with these findings, showing that mothers were primary caregivers for their child with a disability, and that child problem behaviors often occurred in routines in which the father was not present.…”
Section: Discussionsupporting
confidence: 76%
“…Patterson's early work, which examined coercive interaction with mothers, fathers, and siblings, indicated that mothers were the most common partners in coercive exchanges with their aggressive child (Patterson, 1980). Studies of families of children with disabilities show that mothers assume a larger portion of caregiving responsibilities for the child (see Byrne & Cunningham, 1985). Our initial assessment of routines was consistent with these findings, showing that mothers were primary caregivers for their child with a disability, and that child problem behaviors often occurred in routines in which the father was not present.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is consistent with those of other studies (Kaminsky and Dewey 2002) but not consistent with others which suggest that the existence of a CD has a negative effect on siblings (Crnic, Friedrich, and Greenberg 1983;Byrne and Cunningham 1985).…”
Section: Discussionsupporting
confidence: 83%
“…Variables such as the families' socio-economic circumstances or the nature and severity of the child's impairments were rarely considered as possible sources of difference in family response. Byrne and Cunningham (1985) have commented that these failures contributed to the self-fulfilling nature of the assumptions of homogeneity and pathology.…”
mentioning
confidence: 96%
“…These approaches include investigating which families or family members are vulnerable to the stress engendered by the presence of the child, which aspects of caring for the child are stressful, what are the unmet service needs of families, which families cope with and adapt to the stresses and how they do so (Beckman, 1983;Quine and Pahl, 1985;Crnic, Friedrich and Greenberg, 1983;Turnbull, Brotherson and Sumners, 1984;Kornblatt and Heinrich, 1985;Schilling et af., 1984;Chetwynd, 1985Chetwynd, , 1986Kirkham et af., 1986). Byrne and Cunningham (1985) provide a comprehensive review of these studies. Stress experienced by the carers of children with learning difficulties is an important issue because it affects both the well-being of the mothers and the outcome for the children.…”
mentioning
confidence: 98%